2018
DOI: 10.1111/jth.14226
|View full text |Cite
|
Sign up to set email alerts
|

Less abnormal uterine bleeding with dabigatran than warfarin in women treated for acute venous thromboembolism

Abstract: Introduction Although direct oral anticoagulants (DOACs) are associated with a better safety profile than warfarin in patients with acute venous thromboembolism (VTE), direct factor Xa inhibitors involve a higher risk of abnormal uterine bleeding (AUB). We aimed to determine the risk of AUB during anticoagulation with dabigatran compared with warfarin. Methods Post-hoc analysis of the pooled RE-COVER studies and the RE-MEDY trial. Incidences of AUB, based on a defined preferred terms search for adverse events,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…The safety and efficacy of dabigatran in treatment of VTE disease has been well established, and there is ample experience with this specific agent in clinical practice. As opposed to evidence from the post hoc analyses of the factor Xa inhibitor licensing trials, a significantly lower risk of abnormal uterine bleeding in premenopausal women with VTE treated with dabigatran compared with warfarin (OR, 0.59; 95% CI, 0.39–0.90) was found in a recent post hoc analysis of the pooled RE‐COVER‐I, RE‐COVER‐II, and RE‐MEDY trials 13 . Anticoagulant‐associated HMB may be reduced while on thrombin inhibitor compared with VKA, but a thrombin inhibitor has not been compared directly to a factor Xa inhibitor in this context.…”
Section: Rationale For Including Patients With Any Indication For Facmentioning
confidence: 70%
See 2 more Smart Citations
“…The safety and efficacy of dabigatran in treatment of VTE disease has been well established, and there is ample experience with this specific agent in clinical practice. As opposed to evidence from the post hoc analyses of the factor Xa inhibitor licensing trials, a significantly lower risk of abnormal uterine bleeding in premenopausal women with VTE treated with dabigatran compared with warfarin (OR, 0.59; 95% CI, 0.39–0.90) was found in a recent post hoc analysis of the pooled RE‐COVER‐I, RE‐COVER‐II, and RE‐MEDY trials 13 . Anticoagulant‐associated HMB may be reduced while on thrombin inhibitor compared with VKA, but a thrombin inhibitor has not been compared directly to a factor Xa inhibitor in this context.…”
Section: Rationale For Including Patients With Any Indication For Facmentioning
confidence: 70%
“…trials. 13 Anticoagulant-associated HMB may be reduced while on thrombin inhibitor compared with VKA, but a thrombin inhibitor has not been compared directly to a factor Xa inhibitor in this context.…”
Section: Rationale For Including Patients With Any Indication For Fmentioning
confidence: 99%
See 1 more Smart Citation
“…An individual patient data meta‐analysis of the phase 3 trials showed that major bleeding of vaginal origin, although rare, occurred more often with use of factor Xa‐inhibitor than with VKA (17/10595 vs. 3/10957) . In contrast, data from the pooled RE‐COVER and RE‐MEDY trials (n = 1280), in which the effect of direct thrombin inhibitor dabigatran was evaluated, showed an overall AUB rate of 5.9% with dabigatran, compared to 9.6% with VKA (OR 0.6; 95% CI 0.4‐0.9) …”
Section: Periodmentioning
confidence: 95%
“…However, after this time, a temporary dose reduction of rivaroxaban or interruption of anticoagulation for the first days of the menstrual period was found to decrease menstrual bleeding without increasing risk of VTE . Switching treatment from a factor Xa inhibitor to dabigatran may be a reasonable option with regard to heavy menstrual bleeding but requires further investigation …”
Section: Periodmentioning
confidence: 99%